Islamic Education in an Effort to Strengthen the Deradicalization of the Madura Community, East Java, Indonesia - Supandi, Supandi; Ahmad, Ahmad; Subhan, Mohammad (Universitas Islam Madura, 2026)
The purpose of this study is to see how the value of wasathiyah is internalized in Dirasah Islamiyah learning in higher education by using an integrative-reflective learning model. This study was conducted using a mixed approach with sequential exploration design. The conceptual model is formulated through qualitative exploration, and then quantitative testing is carried out through pre-test and post-test of students' moderation attitudes. The research subjects consisted of 72 students and 3 teachers who taught at Dirasah Islamiyah. Observations, in-depth interviews, documentation, reflection journals, and moderation attitude questionnaires based on tawassuth, tawazun, i'tidal, tasamuh, and musawah indicators were used to collect data. The results showed that after applying the integrative-reflective model, students' moderation scores increased significantly; The mean score increased from 3.21 to 3.78 (p < 0.001), and the size of the influence increased in large groups. The results show that students' understanding has shifted from normative concepts to more inclusive moral awareness and social practices. As a mechanism for internalizing values, the integrative-reflective model utilizes text-context dialogue and critical reflection. This study contributes to the development of moderation-based Islamic pedagogy and provides practical advice for improving the Dirasah Islamiyah program in higher education. The goal of the program is to form a generation of Muslims who are moderate, critically thinking, and oriented towards the social good.